Penyuluhan Kesehatan Pada Remaja Putri Tentang Kesehatan Reproduksi Remaja - Diana Dayaningsih; Yuni Astuti; Siswanto Siswanto; Galuh Oktaviani; Nadya Tri Yuwinda; Niken Dwi Rahayu; Heru Khoeruddin (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
Adolescence is a period of human development. Reproductive health in Indonesia which is prioritized only includes four components/programs, namely: maternal and newborn health, family planning, adolescent reproductive health, as well as prevention and control of sexually transmitted diseases (STDs) including HIV/AIDS. The community service that we will carry out refers to the adolescent reproductive health program. Adolescent Reproductive Health is a healthy condition that concerns the reproductive systems, functions and processes of adolescents. The definition of health here does not merely mean being free from disease or free from disability but also being mentally and socially and culturally healthy. Adolescents need to know about reproductive health in order to have correct information about the reproductive process and the various factors that surround it. With the correct information, it is hoped that teenagers will have responsible attitudes and behavior regarding the reproductive process. Adolescent reproductive health problems apart from having a physical impact, can also affect mental and emotional health, economic conditions and social welfare in the long term. Long-term impacts not only affect the teenagers themselves, but also their families, communities and the nation in the end.